2020
DOI: 10.3390/nu12030839
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Akkermansia muciniphila by a Diet Containing Japanese Traditional Medicine Bofutsushosan in a Mouse Model of Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is considered a worldwide healthcare problem that mirrors the increased prevalence of obesity. Gut microbiota plays a crucial role in the progression and treatment of NAFLD. Bofutsushosan (BTS), a pharmaceutical-grade Japanese traditional medicine, has long been prescribed in Japan for obesity and obesity-related syndrome. Although BTS has been reported to exert an anti-obesity effect in obese patients as well as various obesity-model animals, its effect on gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 62 publications
(43 reference statements)
2
11
1
Order By: Relevance
“…The HFD fed mice showed significantly higher AST and ALT levels than ND fed mice. Comparatively, higher levels of AST and ALT of HFD mice were most probably due to obesity generated metabolic abnormality in liver of obese mice [66]. Role of genetic responses could not be ignored in improvement of adipogenic situation during obesity development and propagation.…”
Section: Treatmentsmentioning
confidence: 96%
“…The HFD fed mice showed significantly higher AST and ALT levels than ND fed mice. Comparatively, higher levels of AST and ALT of HFD mice were most probably due to obesity generated metabolic abnormality in liver of obese mice [66]. Role of genetic responses could not be ignored in improvement of adipogenic situation during obesity development and propagation.…”
Section: Treatmentsmentioning
confidence: 96%
“…Dietary intervention in mice on an HFD can increase the abundance of AM [ 142 ]. Interestingly, a large amount of research has shown that while using some substances (including grape polyphenols [ 143 ], epigallocatechin-3-gallate [ 144 ], rhubarb extract [ 145 ], polysaccharides obtained from Cordyceps militaris [ 146 ], protein-bound β-glucan [ 147 ], puerarin [ 148 ], Bofutsushosan [ 149 , 150 ], etc.) to combat obesity, it has also been found that they can regulate the abundance of AM to improve efficacy.…”
Section: Native Probiotics and Diseasesmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a metabolic disorder related to inflammation. Traditional medicine has been demonstrated to improve the liver dysfunction ( Nishiyama et al, 2020 ). Researchers reported that a mixture of aqueous extracts including N. sativa seeds and fenugreek (100 mg/kg) has an improving effect on nonalcoholic fatty liver disease in rats.…”
Section: The Effects Of Medicinal Plants On Metabolic Disordersmentioning
confidence: 99%